A Study on the Comparative Performance of Different Breeds of Broiler Ducks Under Farmer`s Condition at Farming System Research and Development (FSRD) Site, Sylhet, Bangladesh - Bhuiyan, M.M.; Khan, M.H.; Khan, M.A.H.; Das, B.C.; Lucky, N.S.; Uddin, M.B. (International Journal of Poultry Science, 2005)
The experiment was conducted with 40 Pekin, 40 Muscovy and 40 Deshi White day-old as hatched broiler ducklings under farmers condition to investigate the comparative performance of three breeds of ducks under farmer`s management up to the 09 weeks of age. The final live weight in Pekin, Muscovy and Deshi White were 1763.0, 1225.0 and 1208.0 g/ducks respectively (P < 0.05 ). The total feed consumption up to the brooding period in three breeds were 2047.00, 1652.06 and 1430.05 g/ducklings respectively (P < 0.05) and the respective feed conversion ratios were 2.40, 2.91 and 3.05. Mortality was non- significant (P>0.05) among the breeds of ducks. The highest (70%) dressing yield was found from Pekin and the lowest (65%) from Deshi White. The highest production cost was found in Pekin and the lowest in Deshi White. The highest gross margin and BCR (Tk.34.93/duck and 1.66 respectively) were obtained from Pekin and the lowest (Tk. 11.45/duck and 1.23 respectively) from Deshi White. From the results it may be concluded that exotic breeds /improved breeds of broiler ducks rearing is possible at FSRD site, Sylhet and farmers can be benefited within short time. The breed of Pekin ducks is superior over Muscovy and Deshi White.